Alkamides from Echinacea angustifolia interact with P-glycoprotein of primary brain capillary endothelial cells isolated from porcine brain blood vessels - Mahringer, Anne; Ardjomand-Woelkart, Karin; Bauer, Rudolf; Fricker, Gert; Efferth, Thomas (Planta medica, 2013)
The blood-brain barrier prevents the passage of toxic compounds from blood circulation into brain tissue. Unfortunately, drugs for the treatment of neurodegenerative diseases, brain tumors, and other diseases also do not cross the blood-brain barrier. In the present investigation, we used isolated porcine brain capillary endothelial cells and a flow cytometric calcein-AM assay to analyze inhibition of P-glycoprotein, a major constituent of the blood-brain barrier. We tested 8 alkamides isolated from Echinacea angustifolia and found that four of them inhibited P-glycoprotein-mediated calcein transport in porcine brain capillary endothelial cells.
Gesehen am 15.06.2021